Corn‐fermented protein as a replacement for fish meal in diets for Atlantic salmon, Salmo salar, parr: Growth, feed utilization, antioxidant activity, non‐specific immune response, and gut histopathology - Jeongwhui Hong; Jose G. Ortiz; Brian C. Small (Journal of the World Aquaculture Society)
Abstract Fishmeal (FM) is still believed to be the gold standard protein source, especially for high‐value aquaculture species such as salmon. However, due to supply and price fluctuations, coupled with environmental issues in FM production, FM is no longer a sustainable source from economic and environmental perspectives. Recently, high‐protein corn co‐products, such as high‐protein distiller's dried grains (HP‐DDG) and corn‐fermented protein (CFP) have attracted much attention as alternative protein ingredients. Therefore, a 12‐week feeding trial was carried out to assess a CFP product on growth performance, feed utilization, antioxidant and non‐specific immune responses, and intestinal histopathology as an FM replacer in the diets of Atlantic salmon parr, Salmo salar. Five isonitrogenous (51% crude protein) and isocaloric (22.3 MJ kg−1) diets were formulated to substitute 0% (CFP0), 25% (CFP25), 50% (CFP50), 75% (CFP75), and 100% (CFP100) of FM with a corresponding amount of CFP. The experimental diets were fed to satiation, three times daily, to quadruplicate groups of Atlantic salmon parr (11.6 ± 0.06 g). At the end of the 12‐week feeding trial, the final weight, weight gain, and survival of fish did not significantly differ between treatment groups. However, in fish fed CFP100, both the feed conversion ratio (FCR) and the protein efficiency ratio (PER) exhibited significant differences in comparison with those of fish fed other treatments, with FCR being significantly higher and PER being significantly lower. Quadratic regressions of PER and FCR against the dietary CFP inclusion levels suggest that the optimal substitution level was between 18.6% and 25%. Parameters related to antioxidant and non‐specific immune responses were not significantly impacted by the dietary treatment except for lysozyme activity. Lysozyme activity exhibited a significant increase in fish fed CFP25 in contrast to the fish fed CFP75. With respect to distal intestinal morphology, fish fed CFP0 and CFP25 exhibited significantly higher fold height, while fish fed CFP50 showed a reduction in fold height. The mean score of evaluated histopathology features was not significantly influenced by the dietary CFP levels. In conclusion, based on the results of the analysis of variance (ANOVA), replacing 50% of FM with CFP can be implemented without any detrimental effects on growth performance, feed utilization, non‐specific immunity, and intestinal health during the parr phase of Atlantic salmon production.